(untitled) (Global Journal of Human-Social Science, 2017)
Intervention on corpses as a mortuary practice has been reported in South America as early as 9000 BP (Strauss et al., 2015).In the region of the San Francisco River, in Argentine Northwest (NOA), complex forms of burial involving per mortem interventions on the body of the deceased have been reported in recent years. These complexes ritual cover all age classes and include defleshing, evisceration and selection of anatomical parts, associated with fire exposure practices on direct primary burials. The combination of different kinds of perimortem intervention and exposure to fire in direct primary burials seems to represent an idiosyncratic practice that has no parallel in other contemporary populations in Northwestern Argentina, and can therefore